Valor social del anciano - Luna Torres Bertha (Universidad Nacional de Colombia, 1997)
The old age is been surrounded bymisteries, myths and prejuidices. The concepts and the valoration of the ancient man, have been contradictory. In different places and in many cultural moments, the old man has been taken from the glory to the scorn. The actual world scrolls the ancient in a very fast rhythm; the social changes have generayed conditions of disadvantajes for that group of the population, difficulting even more the process of growing old, that in fact has a lot of limitations. Its important that a lot of professionals from many institutions involved with this important cause, join the work developed by geriatrics and gerontologics;  soin this way we can restore the social values of the ancient, who deserves a peacefull old age in compensation with his participation in the job of building a better society. Only in this way, the fear to grow old will be lost. La vejez se ha visto rodeada de tabúes, mitos y prejuicios. Han sido contradictorios los conceptos y la valoración del anciano, quien en lugares y momentos culturales ha estado desde ensalzado hasta despreciado. El mundo actual, desplaza al geronte a ritmo acelerado; los cambios sociales han generado condiciones de marginalidad para ese sector de población, dificultando aun más el proceso de envejecer, que de hecho tiene limitaciones. Es por eso importante que al trabajo que desarrollan geriatras y gerontólogos se sumen otros profesionales y un sinnúmero de entidades; en aras de eliminar prejuicios y rescatar el valor social del anciano, quien por su legado merece un ocaso, que compense su aporte y participación en la construcción de la sociedad, solo así se perderá el miedo a envejecer.